KEMITRAAN PADA PROGRAM PENANGGULANGAN KEMISKINAN PERKOTAAN - Dikson junus (JURNAL LEGALITAS, 2010)
The development approach through the development actors\' initiative and support at lecal level has been a participative-based development model.The initiative and support are encouraged through the establishment of the partnership between people and development actor, including local government and it aims at developing an interaction process in the effort to create a joint movement in alleviating poverty. in the context of people empowerment partnership,those who establish the partnership do not make any differentiation in terms of magnitude or volume, status/legality, or their power. the partnership is linearly established, which means that there is not subordination among them. the study aims at investigating and describing the partnership among actors in the implementation of the P2KP program in Gorontalo city. it is of the kind of qualitave one with descriptive method the data is collected using intrview, obseiatio and secondary data use. The interview is conducted using interview guideline, informal discussion and standard open interview. the results of the study show: (1) the partnership among actors in the implementation of the P2KP program in Gorontalo city indicates the contribution of the actors\' role in alleviatig poverty and hence the involvement of them directly evidences that BMK,people, and other social groups are actually able to make a synergy with the government in the poverty alleviation and (2) the form of the partnership among the actors in the P2Kp program is put in the context of role playing in accordince wifh their respective authority and in the context of join movement. Key words:parnership, empowerment,role,interaction, sharing.